2023
DOI: 10.21037/jtd-22-825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of switching from continuous to bilevel positive airway pressure on sleep quality in patients with obstructive sleep apnea: the prospective POP IN VAuto study

Abstract: Background: Issues with tolerability and side effects can decrease continuous positive airway pressure (CPAP) device usage and the benefits of therapy. Different positive airway pressure (PAP) therapy modes providing expiratory pressure relief or using a different pressure during inspiration vs. expiration (bilevel PAP) may alleviate some of these issues. This multicenter, prospective study evaluated the effects of switching from CPAP to bilevel PAP (VAuto mode) on respiratory parameters, device usage, side ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Six were weaned from MV to BiPAP on day 4, which might have negatively impacted their sleep, due to changes in airflow, mask discomfort, or adjustment difficulties. 36 However, in the subgroup of patients with MV, SWS increased to an hour on days 3 and 5 in the gabapentin group. Our study revealed that SWS as a primary outcome was significantly increased in ICU patients who received gabapentin.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Six were weaned from MV to BiPAP on day 4, which might have negatively impacted their sleep, due to changes in airflow, mask discomfort, or adjustment difficulties. 36 However, in the subgroup of patients with MV, SWS increased to an hour on days 3 and 5 in the gabapentin group. Our study revealed that SWS as a primary outcome was significantly increased in ICU patients who received gabapentin.…”
Section: Discussionmentioning
confidence: 87%
“…This might be because only 15 patients (50% from the beginning) in the gabapentin group were in the ICU until day 5. Six were weaned from MV to BiPAP on day 4, which might have negatively impacted their sleep, due to changes in airflow, mask discomfort, or adjustment difficulties 36 . However, in the subgroup of patients with MV, SWS increased to an hour on days 3 and 5 in the gabapentin group.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive positive pressure ventilation (NIV or NPPV, respectively) is indicated for treatment of CSA and NH but is also a recognized therapeutic option for OSA if CPAP is not tolerated or fails to be effective [89,100,112]. Several criteria have been introduced for indication of NIV in patients with NMDs or thoracic wall disease, all including the presence of NHrelated complaints or clinical symptoms of respiratory muscle weakness [100,101,[113][114][115].…”
Section: Noninvasive Ventilationmentioning
confidence: 99%